2017
DOI: 10.1007/978-3-319-63187-5_5
|View full text |Cite
|
Sign up to set email alerts
|

ROCK and RHO Playlist for Preimplantation Development: Streaming to HIPPO Pathway and Apicobasal Polarity in the First Cell Differentiation

Abstract: In placental mammalian development, the first cell differentiation produces two distinct lineages that emerge according to their position within the embryo: the trophectoderm (TE, placenta precursor) differentiates in the surface, while the inner cell mass (ICM, fetal body precursor) forms inside. Here, we discuss how such position-dependent lineage specifications are regulated by the RHOA subfamily of small GTPases and RHO-associated coiled-coil kinases (ROCK). Recent studies in mouse show that activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Several direct and indirect targets of ROCK1/2 kinases in the early embryo have been described ( Alarcon and Marikawa, 2018 ; Shi et al, 2017 ). Among these is YAP1, a transcriptional partner of TEAD4 ( Nishioka et al, 2009 ), since ROCK activity is required for the nuclear localization of YAP1 ( Kono et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several direct and indirect targets of ROCK1/2 kinases in the early embryo have been described ( Alarcon and Marikawa, 2018 ; Shi et al, 2017 ). Among these is YAP1, a transcriptional partner of TEAD4 ( Nishioka et al, 2009 ), since ROCK activity is required for the nuclear localization of YAP1 ( Kono et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also shown that Rho and Rho-associated coiled-coil kinases 1 and 2 (ROCK1 and ROCK2) are necessary for lineage formation by negatively regulating the Hippo pathway ( Kono et al , 2014 ; Shi et al , 2017 ; Alarcon and Marikawa, 2018 ). ROCK is activated by Rho small GTPases and then it phosphorylates a variety of targets involved in modulation of cellular processes such as cell polarity and gene expression ( Amano et al , 2010 ; Julian and Olson, 2014 ).…”
Section: Cellular and Molecular Mechanisms That Regulate Hippo Signalmentioning
confidence: 99%
“…YAP1/TAZ activation by the Gα 12/13 -RhoA-ROCK axis can promote endothelial cell sprouting, facilitate vascular smooth muscle cell (VSMC) migration and proliferation, and may participate in embryonic vascular development 73 . Furthermore, Rho-ROCK axis promote trophectoderm differentiation and inhibit the formation of the inner cell mass through enhanced YAP1 nuclear localization 84 . Thus, the Gα 12/13 -RhoA-ROCK axis may participate in YAP1/TAZ-mediated cardiac biology.…”
Section: Interaction Of Hippo-yap1/taz Signaling With the Gpcr Pathwamentioning
confidence: 99%